2021
DOI: 10.3389/fonc.2021.792878
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Adverse Events Following Surgery in Patients With Diffuse Lower-Grade Gliomas

Abstract: BackgroundRecently, the Therapy-Disability-Neurology (TDN) was introduced as a multidimensional reporting system to detect adverse events in neurosurgery. The aim of this study was to compare the novel TDN score with the Landriel–Ibanez classification (LIC) grade in a large cohort of patients with diffuse lower-grade glioma (dLGG). Since the TDN score lacks validation against patient-reported outcomes, we described health-related quality of life (HRQoL) change in relation to TDN scores in a subset of patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Landriel classification was modified from the classification of complications by Clavien and Dindo to match the need of neurosurgical patients (Manekk et al 2022 ). Currently, the Landriel classification is the most accepted and practiced in neurosurgery based on the interventions required to manage the complications (Gómez Vecchio et al 2021 ). This is the simplest form of classification that can be used to categorize surgical complications and is easily understood by medical and paramedical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Landriel classification was modified from the classification of complications by Clavien and Dindo to match the need of neurosurgical patients (Manekk et al 2022 ). Currently, the Landriel classification is the most accepted and practiced in neurosurgery based on the interventions required to manage the complications (Gómez Vecchio et al 2021 ). This is the simplest form of classification that can be used to categorize surgical complications and is easily understood by medical and paramedical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Glioma affects patients’ functional status and HRQoL negatively, due to disease- and therapy-related symptoms such as neurocognitive deficits, including visual disorders and communication deficits, disturbed sleep, fatigue, drowsiness, itchy skin, and bladder control issues, and due to associated conditions such as depression and anxiety ( Table 1 ) ( 3 , 46 49 , 66 ). Concerns about HRQoL are the main factor in treatment decisions for up to 81% of patients, of whom 81% and 79% – for low- and high-grade glioma, respectively – are primarily concerned with quality of life, not survival, when deciding on treatment ( 52 ).…”
Section: Burdenmentioning
confidence: 99%
“…Neurological deficits impact 44–50% of patients with glioma before surgery ( 52 , 68 ) and are more than three times more frequent in patients with diffuse glioma than in age- and sex-matched people from the general population ( 68 ), with cognitive performance often declining over time ( 69 ). These deficits have been identified as reducing HRQoL, with new-onset deficits associated with a reduction of 0.17 in EQ-5D 3L index values relative to no deficit in diffuse lower-grade glioma ( 46 ). Data by histology suggested that patients with glioblastoma had worse HRQoL and functioning on domains such as emotion than patients with other glioma (and brain tumors generally) ( 48 ).…”
Section: Burdenmentioning
confidence: 99%